Procedure For Using The Customs Manifest Application In The Inward Manifest Issuance Process At PT. Naval Global Trans Belawan - Ivone Dwimonica Sinaga; Masringgit Marwiyah Nst; Fadiyah Hani Sabila (KALAO'S MARITIME JOURNAL, 2024)
To find out more closely how the company PT. Naval Global Trans Belawan Center, carries out activities on procedures for using the Customs manifest application in the process of issuing the Inward Manifest. This aims to carry out the responsibility in submitting cargo reporting documents to the parties who are truly related and responsible. In the process of loading the Inwad Manifest document, supporting documents such as ship definites and Bill of Lading are required. The ship particular document functions to explain the detailed ship data that will be registered in the manifest module in the transport equipment menu. Meanwhile, the Bill of Lading (B/L) document functions to complete the identity of an item which is useful for expediting the procedure for creating an Inward Manifest document. This is to be supported by the company PT. Naval Global Trans Belawan, in the procedure for making a draft Manifest with the procedure for sending an Inward Manifest with a response BC 1.1 In writing this paper the author used 2 (two) types of research methods in collecting data, namely: Field Observation Method, interviews with employees and Literature Study Method, namely Retrieve data from library books.